1993
DOI: 10.1099/00221287-139-11-2659
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of lipoteichoic acid and peptidoglycan--teichoic acid of Bacillus subtilis 168 (Marburg)

Abstract: To evaluate the suitability of Bacillus subtilis as a production host of heterologous proteins for pharmaceutical purposes, we assessed the biological activity of this bacterium and its major cell envelope components, lipoteichoic acid (LTA) and peptidoglycan-teichoic acid complex (PGTA) in several eukaryotic effector assays. LTA and PGTA were found to be non-toxic for mice and guinea-pigs in a short-term toxicity assay. PGTA was weakly pyrogenic and weakly mitogenic. Both LTA and PGTA acted as immunologic adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Also, its teichoic acid has weak or no biological activity (12). When used as stimulatory proteins in lymphoproliferation assay, the purified protein preparations induced minimal mitogenic activity as shown by relatively low background levels observed in proliferative response of splenocytes from naïve or mock-immunized mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, its teichoic acid has weak or no biological activity (12). When used as stimulatory proteins in lymphoproliferation assay, the purified protein preparations induced minimal mitogenic activity as shown by relatively low background levels observed in proliferative response of splenocytes from naïve or mock-immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…The widely used laboratory strain 168 contains no innate toxins; in particular, since it is gram positive there is no lipopolysaccharide endotoxin. Its cell wall components are of weak or no biological activity (peptidoglucan and teichoic acid) (12). Effective expression systems for heterologous proteins are available, with the choice of intracellular or secreted mode of production.…”
mentioning
confidence: 99%
“…10,11 Indeed, polymeric PGN was considered to be unable to stimulate innate immune cells 10,11 and intestinal epithelial cells. 32 Because PGN does not stimulate TLRs and because it causes only minimal pathological changes in mice, [33][34][35][36] PGN has often been overlooked as a pathogen-associated molecular pattern. However, a recent body of work from our laboratory demonstrates the importance of PGN as a pathogen-associated molecular pattern when anti-PGN IgG is present.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that LTA elicits tumor necrosis factor a (TNF-a) release, inducible nitric oxide synthase (iNOS) induction, and circulatory failure in anesthetized rats (15). However, in contrast to LPS, LTA or PepG does not cause lethality or organ toxicity at an immunostimulatory dose in mice or rats (16)(17)(18)(19).…”
mentioning
confidence: 99%